Measurement of Wear of Acetabular Liner by 3D Coordinate Measuring Machine - Pham, Ngoc Tuan; Nguyen, Van Tuong (Old Journal, 2019)
Wear is one of important factors to evaluate the quality and service life of total hips. This paper presents the wear test of a UHMWPE acetabular liner which was made in Vietnam. The wear of the acetabular liner was defined by the dimensional change method according to ISO 14242-2. The volume of the acetabular cavity was measured prior to the start of the wear test and at suitable intervals during the test. A coordinate measuring machine was used to get the coordinates of points on the surface of the acetabular cavity. From the measured data, the 3-dimensional model of the acetabular cavity was created to calculate its volume before and after several wear tests. The results of the wear test showed that the average wear of the acetabular liner is 29.4 mm³/10⁶ cycles. Compared to some published studies, the acetabular liner of this study had a low wear and was in the range of typical wear of similar acetabular liners.